The modulation of multidrug resistance in ovarian cancer patients - Miedzińska-Maciejewska, Magdalena; Bodnar, Lubomir (Contemporary Oncology/Współczesna Onkologia, 2004)
Ovarian cancer is ubiquitously diagnosed in Poland with morbidity of 11 new cases per 100 000 annually. Despite the high response rates with initial chemotherapy, the five-year survival rate from ovarian cancer is only 20% to 30%. Most patients with ovarian cancer relapse and the response rate for the secondary treatment remains disappointingly low. The main problem and reason for these low cure rates are the selection of tumor cell clones that are resistant to cytotoxic drugs. It is so called the multidrug resistance connected with a decreased susceptibility to apoptosis. There are many studies dealing with drug resistance and the ways of overcoming it, including the escalation of cytostatics doses, high dose chemotherapy with autologous stem cell transplantation, multidrug chemotherapy, gene therapy (two types: (1). gain-of-function and (2). loss-of-function), inhibition of the tumor angiogenesis or using different pharmacological substances, which are called due to their function, resistance modulators, modifiers or chemosensitizers. Modulators function through targeting multidrug resistance genes or any other mechanisms not completely known yet. We can increase cytotoxicity without increasing the drug dose when the modulator is given simultaneously. It is expected that modulators can increase efficacy of conventional chemotherapy. This article presents an overview of different studies on basic modulators of drug resistance in ovarian cancer and their clinical significance.